Are You Ready for Your Close-Up? Creating a Library Promotional Video. Issue 2 (3rd April 2019) - Bremer, Peter
ABSTRACT: Learn how to create a promotional library video for your library using the multimedia software Camtasia. Challenges and lessons learned are explored by detailing one reference librarian's efforts at creating a Ask A Librarian video.